SURVEY KUALITAS PRODUKSI BETON DAN EVALUASI DI PROYEK (STUDY KASUS PADA SETIAP PROYEK) - Andres Mulianta Saragih (LP2MTBM MAKARIOZ, 2018)
The present state of the technology and design of structural lighweight aggregate concrete are summarized.From aggregates for concrete to made process to structure of building must be there to The finish of theproject is good and strongth property and performance of the building. With good check and good evaluationof concrete quality, then we can get good property and good performance of building structure in the project